Epigenetic Regulation in Gastroenteropancreatic Neuroendocrine Tumors - Crabtree, Judy S. (Frontiers in Oncology, 2022)
Gastroenteropancreatic neuroendocrine neoplasms are a rare, diverse group of neuroendocrine tumors that form in the pancreatic and gastrointestinal tract, and often present with side effects due to hormone hypersecretion. The pathogenesis of these tumors is known to be linked to several genetic disorders, but sporadic tumors occur due to dysregulation of additional genes that regulate proliferation and metastasis, but also the epigenome. Epigenetic regulation in these tumors includes DNA methylation, chromatin remodeling and regulation by noncoding RNAs. Several large studies demonstrate the identification of epigenetic signatures that may serve as biomarkers, and others identify innovative, epigenetics-based targets that utilize both pharmacological and theranostic approaches towards the development of new treatment approaches.